La critique du droit romain et la philosophie du droit dans les œuvres des Pères de l’Église Tertullien et de Lactance - Amar Laidani (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
The author analyses the influence exerted by roman law and rhetoric on the apologetic works of Tertullian and Lactantius. However, their relationship to theses arts remained problematic. That’s why the author in the first part illustrates the way in which the two aforementioned Church Fathers, Tertullian and Lactantius, in order to resolve this dilemma had criticized secular rhetoric and its limits. In the second part he illustrates how the latter developed their reflection about key concepts such as natural law and justice through the art of rhetoric.